ON WEAKLY SEMI OPEN SETS IN TOPOLOGICAL SPACES - Sajjanara, Veeresha A (Journal of Global Research in Mathematical Archives(JGRMA), 2017)
In this research paper, a new class of open sets called weakly semi open sets (ws- open sets) in topological spaces are introduced and studied.Â  This new class of sets lies between the class of all semi-open sets and generalised semi-pre regular open sets in topological spaces. Also some of their properties have been investigated